Peran Bank Dunia Dalam Pengelolaan Hutan Indonesia Di Era Reformasi - Asep Saepudin (Jurnal Paradigma, 2011)
This Paper describe that world bank's role in forestry management in indonesia have changed. In new order era, the world bank's role in indonesia forestry has given opportunity for increasing forest degradation. It was caused by strategy and policy of world bank for developed that three goal, economics growth, population growth, and poverty reduction in java islands specially without considering social and environment aspects. Development of sustainable development paradigm in global level, has effect world bank to change orientation, strategy, and policy in forestry. SOme of them are through optimizing the forest potential decrease poverty, integration between forest aspect with economy sustainable development protection of forest global value and the loan scheme reformation.